Resolva a expressão:
(• multiplicação)
a)3+1•(2-1)-4+(3•2+1)=
b)16-36•(1+3)+43-2•7=
c)42-25+(3•2-2)+(3•4-5)
d)126+42-98+(3•12-3)=
e)76-33+8•9-12=
f)106-46-24+4•13=
qual é a resposta?
Respostas
respondido por:
2
Resposta:
a) -5
b) 522
c) 28
d) 103
e)103
f) 304
Explicação passo-a-passo:
a) 4.(-2) -4 +7= -8 -4 +7= -5
b) -20.4 +43.14= -80+ 602= 522
c) 17 +4 +7= 21+7= 28
d) 168-98 +36-3= 70 +33= 103
e) 43+72 -12= 115-12= 103
f) 60-28.13= 60 -364= 304
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás